Investigation of Students’ Opinions on Distance Education in the COVID-19 Pandemic Process - Ebru Güzel Kuyucu; Serkan Kabak (Journal of Educational Issues, 2024)
Due to the worldwide COVID-19 epidemic, distance education has become a necessity rather than a choice in order to ensure the continuity of education at all educational levels. This research was carried out to examine the opinions of students on the distance education process applied in universities during the COVID-19 Pandemic period. Sample of study consists of 153 students (73 female, 80 male), who were selected by simple random sampling method, studying at Trabzon University Faculty of Sport Sciences. In the study, Opinions for Distance Education Scale (OFDES) and personal information form were used. The scale was developed by Yıldırım et al. (2014) and consists of 18 items and 4 factors. Data were collected through an online survey. The collected data were analyzed with the SPSS program. Descriptive statistics, T-Test and ANOVA analyses were used in the research. It shows that students’ satisfaction with distance education conducted during the COVID-19 epidemic is at a low level (x̄ = 2.03; Sd = .55). In other words, students prefer face-to-face education to distance education. In the gender variable, it was determined that male students (x̄ = 2.75; Sd = .54) had a higher mean score than female students (x̄ = 2.48; Sd = .53). In the study, some suggestions have been developed in order to make the distance education process more efficient from the students’ perspective.